Existential Anxiety, Freedom, and Authenticity: Rollo May's Reading of Annie Baker's Infinite Life - Elaf Muther Muslim (Academia Open, 2026)
General Background: Existential psychology examines human anxiety, freedom, and authenticity as central aspects of lived experience. Specific Background: Annie Baker’s Infinite Life (2023) portrays five women enduring chronic illness while confronting psychological and existential struggles in a healthcare setting. Knowledge Gap: Previous studies have discussed the play broadly but have not analyzed it through Rollo May’s existential concepts. Aims: This study analyzes the representation of existential anxiety, freedom, and authenticity in the play using Rollo May’s theoretical framework. Results: The findings show that the characters’ suffering reflects anxiety of nothingness, the burden of choice, and the pursuit of authentic existence despite physical limitations; anxiety is depicted not merely as negative but as a constructive force leading to self-awareness, responsibility, and meaning-making. Novelty: This study offers a focused existential-psychological reading of Infinite Life grounded specifically in May’s concepts, highlighting anxiety as a transformative element within contemporary drama. Implications: The analysis suggests that confronting existential anxiety enables individuals to move toward authenticity and responsible freedom, contributing to literary criticism and existential psychotherapy discourse. Highlights:• Anxiety is presented as a pathway toward self-awareness and meaning• Character struggles illustrate tension between choice and responsibility• Suffering functions as a route to genuine self-realization Keywords: Existential Anxiety, Authenticity, Freedom, Rollo May, Infinite Life